Improvement of asset accounting in agriculture in the context of digitalization of the economy - Egamberdieva Salima Raimovna (THE INNOVATION ECONOMY, 2026)
The article develops proposals on the composition of balance sheet assets of agricultural enterprises based on international accounting and financial reporting standards. It is proposed to detail fixed assets in the balance sheet by type (class), including such items as investment property. The article presents proposals for improving the organizational and methodological aspects of accounting for fixed assets in agriculture